RETRACTED: Dynamics of a beam with variable cross-section protected from vibration - Dusmatov Olimjon; Khodjabekov Muradjon; Kasimova Feruza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001